Development of Business Model Digital Fraction Property Investment - Desyanta, I Gede Putu Rahman; Darma, Gede Sri (Jurnal Entrepreneur dan Entrepreneurship, 2020)
Investing a property or real estate could be a challenge for Millennials generation. The increase in property prices is not in line with the increased of minimum wage that makes Millennials only afford to rent the property. To having an investment in property need more time in legal procedure, sometime need more than months. Fraction Property investment is a concept of investing property together. Separate the property in other format of digital assets distributed it to all more than one party. To implement this concept need to has a suitable business model and technology. Rising of industrial revolution 4.0, introduce the world with Blockchain Technology. The research is aiming to give better picture of new business model of investing on a property based on blockchain technology. With right business models, millennials generation will have another methods of investment on a property, that secure, easy and digital.